Holy War The History of an Idea. - Ruelland, Jacques G.; Fuykschot, Cornellia; Poulin, Jeanne (Lewiston : Edwin Mellen Press, 2007)
Though the wise know that history will inevitably repeat itself, mankind keeps on making the same mistakes. It is never an easy task to write about war and religion, and Dr. Jacques G. Ruelland has managed to do so clearly and without prejudice. Through his exposé of the holy wars, this philosopher-historian traces a not-so-holy picture of civilization by analyzing the semantics of "sacredness" inherent to monotheistic religions. With the compassionate eye of the humanist, he helps us understand the origins of the justifications of wars waged in the name of the Almighty. Will we ever learn to
Description based upon print version of record.
Keywords: Crusades; Jihad; War -- Biblical teaching; War -- Religious aspects -- Christianity; War -- Religious aspects -- Islam; War -- Religious aspects -- Christianity; War -- Religious aspects -- Islam; Crusades; Jihad; RELIGION / Religion, Politics & State; Electronic books